Respuesta :

Step-by-step explanation:

Prove the following?

cos7x+cos5x+cos3x+cosx=4cosxcos2xcos4x

2

SEE ANSWERS

Answer

3.4/5

36

LHS=cos7x + cos5x + cos3x + cosx

=2cos[(7x+5x)/2].cos[(7x-5x)/2] + 2cos[(3x+x)/2].cos[(3x-x)/2]

[∵ cosA + cosB = 2.cos[(A+B)/2].cos[(A-B)/2]]

=2cos[(12x)/2].cos[(2x)/2] + 2cos[(4x)/2].cos[(2x)/2]

=2cos 6x.cosx+2cos2x.cosx

=2cosx(cos 6x+ cos 2x)

=2.cosx(2cos[(6x+2x)/2].cos[(6x-2x)/2]

=2.cosx(2cos4x.cos2x)

=4.cosx.cos2x.cos4x

=RHS.

hope this helps you!!!!! :))))))))

ACCESS MORE